CLASSROOM MANAGEMENT OF ENGLISH TEACHERS IN TEACHING ENGLISH AT VOCATIONAL HIGH SCHOOL - Intan, Angel Sophia; Astika, Yulia Wiji; Wismar, Teta (Dharmas Education Journal (DE_Journal), 2024)
This research aims to understand how teachers implement classroom management principles in the teaching and learning process at SMKN 10 Bungo and why teachers implement these principles in their students' teaching and learning processes. practice. This type of research is qualitative research, where the data source is the result of classroom observations and interviews. The subjects of this research were three English teachers in grades ten, eleven and twelve. Collected data are grouped according to the research objective, then described and analyzed to get actual data. Research results show that not all English teachers at SMKN 10 Bungo fully apply the principles of classroom management in the teaching and learning process at 3 stages before the activity, during the activity and after the activity. Almost all classroom management principles are implemented during operation. Before and after the activity, teachers only followed three principles of classroom management: enthusiasm, enthusiasm, emphasizing positive things and promoting self-discipline. Research results also find out the reasons why teachers apply classroom management principles, specifically to increase student motivation and improve learning outcomes. Based on the results of this research, it can be concluded that classroom management principles have not been fully implemented by English teachers at SMKN 10 Bungo. Therefore, English teachers need to improve their knowledge of classroom management principles in teaching English. In the hope, this research can make a useful contribution to English teachers in education.